2001
DOI: 10.1080/10473289.2001.10464321
|View full text |Cite
|
Sign up to set email alerts
|

A Fungal Vapor-Phase Bioreactor for the Removal of Nitric Oxide from Waste Gas Streams

Abstract: Ground-level O 3 formation is becoming a major concern in many cities due to recent tightening of O 3 regulations. To control O 3 formation, more efficient treatment processes for O 3 precursors, such as NO x and volatile organic compounds (VOCs), are needed. One promising new technology for removing both NO x and VOCs from offgas streams is biofiltration, a simple process whereby contaminated air is passed through a biologically active packed bed. In this study, a toluene-degrading fungal bioreactor was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 11 publications
1
13
0
2
Order By: Relevance
“…García-Peña et al (2001) observed EC close to 260 g m À3 reactor h À1 with removal efficiency (RE) of 98%, within 30 days of start-up. Woertz et al (2001) also used a fungal biofilter for toluene elimination, which was used as a carbon source and energy for the aerobic elimination of nitric oxide in the gas phase, obtaining RE of 93% with inlet concentration of 250 ppmv of nitric oxide, and a residence time of 1 min for a toluene load of 90 g m In general, start-up takes long time in fungal biofilters as these microorganisms have relatively slow growth rates which is further reduced by the low bioavailability of the substrate due to their relatively low concentrations in air and to their limited solubility in the aqueous biological active phase. The slow attainment of the steady-state condition implies that the biofilter has to be operated with low efficiencies during this period.…”
Section: Introductionmentioning
confidence: 97%
“…García-Peña et al (2001) observed EC close to 260 g m À3 reactor h À1 with removal efficiency (RE) of 98%, within 30 days of start-up. Woertz et al (2001) also used a fungal biofilter for toluene elimination, which was used as a carbon source and energy for the aerobic elimination of nitric oxide in the gas phase, obtaining RE of 93% with inlet concentration of 250 ppmv of nitric oxide, and a residence time of 1 min for a toluene load of 90 g m In general, start-up takes long time in fungal biofilters as these microorganisms have relatively slow growth rates which is further reduced by the low bioavailability of the substrate due to their relatively low concentrations in air and to their limited solubility in the aqueous biological active phase. The slow attainment of the steady-state condition implies that the biofilter has to be operated with low efficiencies during this period.…”
Section: Introductionmentioning
confidence: 97%
“…23 A wide variety of organisms are known to denitrify, including some bacteria, fungi, and simple eukaryotes. 24 Abiotic Reaction. The gas-phase thermal conversion of NO into NO 2 is given by the following equation:…”
Section: Discussionmentioning
confidence: 99%
“…They also indicated that higher NO removal efficiency could be obtained by increasing the toluene supply to the biofilters and|or under lower oxygen concentration in the air (which is typical of combustion off-gas streams). Later, Woertz et al (2001) used a toluene-degrading fungal biofilter and obtained significantly higher NO removal rate (93% at the inlet concentration of 250 ppmv). Okuno et al (2000) also reported up to 80% NO removal in a soil-based biofilter, operating under aerobic conditions.…”
Section: Biofiltration Of Nitrogen Oxidesmentioning
confidence: 98%
“…The difficulty associated with maintaining anaerobic condition (and|or very low oxygen content) in biofilters designed for industrial applications prompted several researchers to investigate the feasibility of aerobic NO removals in biofilters (du Plessis et al 1997;Okuno et al 2000;Woertz et al 2001). Du Plessis et al (1997) used an aerobic toluene-removing biofilter and obtained up to 60 ppmv NO removal under aerobic conditions (17% v|v O 2 ).…”
Section: Biofiltration Of Nitrogen Oxidesmentioning
confidence: 99%
See 1 more Smart Citation